Idiopathic pneumatosis intestinalis secondary to lactulose use in patients with cirrhosis. Issue 6 (9th December 2019) - Varelas, Lee J; Klinge, Matthew J; Malik, Shahid M; Borhani, Amir A; Neal, Matthew
Abstract: Background and Aim: Few case reports exist that link lactulose use with pneumatosis intestinalis in cirrhotics. This study investigates the relationship between lactulose use and idiopathic pneumatosis intestinalis in a cohort of cirrhotic patients. Methods: This case series considers several notable cases of patients with idiopathic pneumatosis intestinalis and concurrent lactulose use. Idiopathic pneumatosis intestinalis was defined as pneumatosis intestinalis with no identifiable etiology. A cohort of 119 patients with cirrhosis and pneumatosis intestinalis were identified in a tertiary care setting, via chart review by a multidisciplinary team. Eleven of these patients were found to have idiopathic pneumatosis intestinalis. Nine of these patients were being treated with lactulose. Results: Six out of 9 patients with idiopathic pneumatosis intestinalis that were being treated with lactulose saw resolution of pneumatosis intestinalis following discontinuation of treatment. Conclusions: The etiology of idiopathic pneumatosis intestinalis is likely multifactorial, but lactulose might play a preventable role in its formation.